Comparison of the Effect of Intra‑articular Injection of Methylprednisolone Alone and in Combination with Combined Ketamine in Pain Reduction in Patients with Knee Osteoarthritis - Sadoni, Hanon (Asian Journal of Pharmaceutics (AJP), 2017)
Background and Objective: Pain is a common complaint in knee osteoarthritis (OA) and the main cause of functional disabilities among middle‑aged and older persons. The conventional treatments are medications, administered in long‑term and are costly with significant side effects. Therefore, it is necessary to develop new efficient therapeutic approaches part icularly those ones that allow the patients to continue their work. The present study aimed to comparatively investigate the pain relieving efficacy of intra‑articular injection of methylprednisolone alone and combined ketamine‑methylprednisolone in patients with knee OA. Materials and Methods: This is a double‑blind clinical trial conducted on patients with knee OA. Seventy patients were randomly divided into two treatment groups (each group 35 cases aged 40‑73 years old) of control and case groups. The control group received 40 mg methylprednisolone and 1 ml of distilled water and the case group received 40 mg of methylprednisolone along with ketamine (0.5 mg/kg) intra‑articularly. The pain perceived by the patients was assessed using a visual analog scale (VAS) (at three‑time points: Before injection, 1 month, and 3 months after injection). The amount of pain reduction was compared pre‑ and post‑injection in each group and between the two groups. Results: The pain reduction in the control and case groups was the same at the 1st month. The pain VAS score in the control group at the 3 month follow‑up showed gradually increased. Conclusion: The VAS pain score showed a higher level of stability in the reduction of pain intensity in case group and these people experienced the reduction in the severity of pain for a longer time.